Relasi Pengusaha-Penguasa Dalam Demokrasi: Fenomena Rent Seeker Pengusaha jadi Penguasa - Muhammad Ali Azhar (PUBLICA, 2012)
Reform has opened up opportunities for entrepreneurs to fill vacancies in the government leadership. That is, because the election can not be denied in addition to requiring figures, intellectuals, also takes charge. The tendency is then driven by a ban on civil servants, military, police and politics since the reforms initiated. This success encouraged the expectation that the next number of employers who will be ruler of the greater. Some key findings in this paper, as analyzed in several phenomena: First, the recognition that entrepreneurs are middle class people who are needed to fill the vacancy of the public that in the past many occupied by civil servants, military and police. Second, the employer is considered to have more opportunities and capability compared with other community groups to win political support as well as in managing the administration of the state. Third, the future of Indonesias political future will be characterized by the role of the entrepreneur.